2008
DOI: 10.1007/s12160-008-9053-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of Asthma Self-efficacy to Asthma Control and Quality of Life

Abstract: Findings suggest that being confident in one's ability to control asthma symptoms is associated with better asthma control and quality of life. Future studies should assess the direction of the association between self-efficacy and asthma morbidity in order to determine optimal treatment targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 32 publications
(41 reference statements)
0
43
1
6
Order By: Relevance
“…Studies have suggested that people's personality may influence their level of asthma control and adherence to asthma medications [7]. Similarly, self-efficacy is a correlate of both asthma control and adherence [8,9]. However, studies conducted thus far are limited, and currently there are no published studies investigating the relationship between self-efficacy and personality in asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that people's personality may influence their level of asthma control and adherence to asthma medications [7]. Similarly, self-efficacy is a correlate of both asthma control and adherence [8,9]. However, studies conducted thus far are limited, and currently there are no published studies investigating the relationship between self-efficacy and personality in asthma.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Self-efficacy is an important determinant of health behavior, associated with positive quality of life among patients living with chronic illnesses. 12,13 The construct of self-efficacy is derived from Bandura's social-cognitive theory, which considers that individuals' perceptions of their own capabilities play a key role in changing their behaviors, motivations and experiences. 14 Thus, self-efficacy is generally defined as an individual's confidence in his or her ability to do a specific task or achieve certain outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have obtained similar results as well as a reduction in long-term morbidity in adults and children, daytime symptoms, use of drugs for asthma and frequency of psychiatric comorbidities [31,32]. They have also shown an improvement in medication adherence, quality of life, quality of sleep, cognitive ability and self-esteem, and a reduction in the feeling of handicap related to asthma [33]. This point may be an important issue when considering cost/benefit issues.…”
Section: Discussionmentioning
confidence: 74%
“…Patients' self-esteem, related to the patient's perceived self-competence, influences stress levels and symptom severity in subjects with chronic illnesses, such as asthma. Self-competence is associated with better asthma control and quality of life [33][34][35]. Aiming at patient's empowerment is thus a key element of self-management.…”
Section: Discussionmentioning
confidence: 99%